The Meaning of Work-Life Balance for Gen Z Employees at Ranch Market Supermarket Menteng Park Branch - Silaban, Trosahlan; Dwianto, Agung Surya (Jurnal Ragam Pengabdian, 2026)
The changing characteristics of the workforce dominated by Generation Z are encouraging organizations to pay more attention to the importance of work-life balance, particularly in the supermarket retail industry with its shift-based work system. This study aims to analyze the meaning of work-life balance for Generation Z employees at Ranch Market, Menteng Park Branch. The study used a qualitative approach with a phenomenological method. Data were obtained through in-depth interviews with six informants and analyzed using Reflexive Thematic Analysis by Braun and Clarke. The results show that work-life balance is defined as the ability to maintain a balance between work and personal life through time management, fulfilling the need for rest, health, social relationships, and personal activities. This experience is influenced by the shift work system, workload, overtime, and limited workforce. While organizational support through flexible leave, good communication, and superior attention are factors that help create balance. This study concludes that work-life balance contributes to the physical, psychological, and social well-being of employees, so companies need to implement more flexible and adaptive work policies to support the well-being and improve the performance of Generation Z employees.